Roles of Type VI Secretion System in Transport of Metal Ions - Yang, Xiaobing; Liu, Hai; Zhang, Yanxiong; Shen, Xihui (Frontiers in Microbiology, 2021)
The type VI secretion system (T6SS) is a transmembrane protein nanomachine employed by many gram-negative bacteria to directly translocate effectors into adjacent cells or the extracellular milieu, showing multiple functions in both interbacterial competition and bacteria-host interactions. Metal ion transport is a newly discovered T6SS function. This review summarizes the identified T6SS functions and highlights the features of metal ion transport mediated by T6SS and discusses its regulation.